HPLC fingerprint of flavonoids, enzyme inhibition and antioxidant activity of Newbouldia laevis stem-bark: an in vitro and in silico study - Kingsley O. Omeje; Benjamin O. Ezema; Chiemeka N. Onaebi; Samson C. Onoyima; Timothy P. C. Ezeorba; Sabinus O. O. Eze (SpringerOpen, 2023)
Abstract Background Medicinal plant contains multiple bioactive compounds with therapeutic potentials. Due to their availability, affordability, and minimal known side effects, they are widely practiced. Identification, quantification, and establishment of their interaction with physiological enzymes help in the standardization of plant-based medicinal extracts. In this study, gas chromatography/flame ionization detector (GC-FID) and high-performance liquid chromatography (HPLC) analysis were used to determine the bioactive components in the ethanol extract of Newbouldia laevis stem bark. The antioxidant activity of the extract was determined. Enzyme inhibitory potency of the flavonoids' components was investigated against acetylcholinesterase, butyrylcholinesterase, phospholipase A2, α-glucosidase, and α-amylase. Results Analysis of ethanol extract of N. laevis stem-bark revealed alkaloids (0.37%), tannins (1.82 mg/TEq/g), flavonoids (5.85 mg/QEq), steroids (0.11 mg/10 g) and glycosides (0.08 mg/10 g). The HPLC fingerprint of flavonoids showed high concentrations (mg/100 g) of catechin (47.11), apigenin (15.68), luteolin (18.90), kaempferol (41.54), and quercetin (37.64), respectively. In vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging ability of the extract was exhibited at 150 and 200 mg/mL, respectively. At 300 mg, most in vitro antioxidant potentials (lipid peroxidation, metal chelating ability, hydroxyl, nitric oxide, sulfide oxide radicals scavenging abilities) were obtained. The extract showed varying inhibitory abilities (> 50%) on acetylcholinesterase, butyrylcholinesterase, phospholipase A2, α-glucosidase and α-amylase at 300 mg/mL, IC50 of 129.46, 237.10, 169.50, 251.04 and 243.06 mg/mL, respectively, with inhibition constants (Ki) of 3.92, 1.63, 1.11, 2.95 and 2.11. Results showed an affinity for the targeted enzymes with free energies higher than the standard drugs. Conclusion The results revealed that the N. laevis stem bark possesses antioxidant activity and enzyme inhibitory activity on the physiological enzyme that has been implicated in diabetes. In vitro and in silico inhibition of these physiological enzymes by extract suggests that the stem bark can be effective in ameliorating the complications associated with diabetes mellitus.